Implementasi E-Tilang Sebagi Wujud Perkembangan Hukum di Kota Malang - Purborini, Vivi Sylvia; Kasmin, Kasmin; Suryanatha, Ida Bagus (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Riau, 2025)
This article discusses technological innovation in public services in the era of industrial technology. In the current context, the Indonesian National Police (Polri) has initiated the ETLE or Electronic Traffic Law Enforcement program as a breakthrough in the framework of electronic road traffic law enforcement. The data analysis technique used in this study is qualitative analysis. The problem approach used in this study is to use socio-legal research. The findings in the writing explain that E-TLE (Electronic Traffic Law Enforcement) created by the Malang City Police Traffic Unit as a technology-based law enforcement model is one form of legal progressiveness to answer the demands of the community in facing current legal problems. In the E-TLE law enforcement system, the public does not need to have direct contact with officers in the field so that vulnerability to corrupt practices can be avoided. In addition, handling legal processes related to traffic violations becomes easier by paying fines directly at the Bank so that the public does not need to come to court at the local District Court.